FOURIER’S ROWS IN COMPUTER GRAPHICS - Криштопа, Людмила Іванівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The paper is devoted to application of the Fourier’s rows in computer graphics as two measured images can be represented, as a two measured signal, in spite of the fact that in an analog form this signal is endless, in discrete he is marked only in the points of bitmapped image. The algorithm of compression, used at format of saving of the JPEG image, is offered and developed, built on the basis of discrete cosines transformation, in avoidance of the Gibbs phenomenon. Actuality of researches of the periodic functions decomposed on a spectrum is grounded, that is the physical analogue of mathematical expositions.